Upaya Meningkatkan Hasil Belajar Peserta Didik melalui Penerapan M-Learning Berbasis Android dengan Pembelajaran Kontekstual - Kalimatus Sadiyah; Riza Yonisa Kurniawan; Moch. Sohibul Anhar (Nusantara: Jurnal Pendidikan Indonesia, 2023)
In the era of development of the Industrial Revolution 4.0, information technology has a big influence on the world of education. However, many students do not use their smartphones in the learning process, so their learning outcomes are still low. This research is classroom action research which aims to improve learning outcomes by implementing m-learning with a contextual approach. The subjects of this research were 35 students in class X-7 of Senior High School 18 Surabaya using a collaborative model carried out in 2 cycles and 4 stages, namely planning, implementing, carrying out actions, observing, and reflecting. Data collection methods are carried out through observation, tests, and documentation. The data analysis technique was carried out descriptively and quantitatively. The results of the analysis show an increase in the learning process from before the action (pre-cycle) to cycles I and II. In cycle I the average score was 75.42 and the percentage of completeness was 71.42%; Then it increased in cycle II with an average score of 93 and a completion percentage of 100%. It can be concluded that the application of m-learning with a contextual approach has succeeded in improving student learning outcomes. The completion presentation reaches 100% of the completion score based on the Merdeka Curriculum KKTP of 75.0.